Prognostic Significance of Signet Ring Cells in Gastric Cancer: The Higher Proportion, The Better Survival - Li, Yang; Zhong, Yuxin; Xu, Quan; Zhu, Zhikai; Tian, Yantao (Frontiers in Oncology, 2021)
BACKGROUND Due to the definition of gastric signet ring cell cancer (GSRC) is still controversial in past decades, the prognosis affected by the proportion of signet ring cells within gastric cancer is uncertain. This study compared the clinicopathological features and prognosis of GSRC with the various proportions of signet ring cells. METHODS We collected GSRC cases without metastasis who underwent curative (R0) resections between 2011 and 2018. Individuals who were low proportion signet-ring cells group (LSRC, <50%) were matched to those who were high proportion signet-ring cells group (HSRC, >50%) through propensity score matching (1:1). We used Cox proportional hazards regression to calculate the adjusted hazard ratios (HR) and 95% confidence intervals (CI) and explored interactions with gender and stage. RESULTS We 1:1 matched individual including 231 cases from LSRC group and 231 cases from HSRC group. Patients with HSRC had a significant higher overall survival rate in multivariable model (aHR=0.56, 95%CI=0.38, 0.84) as compared with those with LSRC. The association of HSRC appeared to be more substantial among individuals at early stage and N0 stage (p-interaction<0.01). CONCLUSIONS This study confirms the GSRC with different proportions of signet ring cells could affect the patient’s survival. Further clinical studies should be developed in the future to provide an appropriate treatment strategy for GSRC.